Micro-RNA 150-5p predicts overt heart failure in patients with univentricular hearts. - Masood Abu-Halima; Eckart Meese; Mohamad Ali Saleh; Andreas Keller; Hashim Abdul-Khaliq; Tanja Raedle-Hurst (PLoS ONE, 2019)
Background In patients with left heart failure, micro-RNAs (miRNAs) have been shown to be of diagnostic and prognostic value. The present study aims to identify those miRNAs in patients with univentricular heart (UVH) disease that may be associated with overt heart failure. Methods A large panel of human miRNA arrays were used to determine miRNA expression profiles in the blood of 48 UVH patients and 32 healthy controls. For further selection, the most abundantly expressed miRNA arrays were related to clinical measures of heart failure and selected miRNAs validated by polymerase chain reaction were used for the prediction of overt heart failure and all-cause mortality. Results According to microarray analysis, 50 miRNAs were found to be significantly abundant in UVH patients of which miR-150-5p was best related to heart failure parameters. According to ROC analysis, NT-proBNP levels (AUC 0.940, 95% CI 0.873-1.000; p = 0.001), miR-150-5p (AUC 0.905, 95% CI 0.779-1.000; p = 0.001) and a higher NYHA class ≥ III (AUC 0.893, 95% CI 0.713-1.000; p = 0.002) were the 3 most significant predictors of overt heart failure. Using a combined biomarker model, AUC increased to 0.980 indicating an additive value of miR-150-5p. Moreover, in the multivariate analysis, a higher NYHA class ≥ III (p = 0.005) and miR-150-5p (p = 0.006) turned out to be independent predictors of overt heart failure. Conclusion In patients with UVH, miR-150-5p is an independent predictor of overt heart failure and thus may be used in the risk assessment of these patients.